A review on the effects of various elemental doping and nanostructuring of β-FeSi2/Si composites on the thermoelectric performance enhancement. (2022) - Binti Abdullah Zaik, Aisyah; Liana Binti Mohd. Redzuan, Farah; Ahmad Zaki Bin Shaikh Salim, Sheikh; Faiz Bin Mohammad, Ahmad; Fitri Bin Mohd. Yakub, Mohd.; Takeda, Masatoshi
Abstract: Thermoelectric device is a transformative technology for renewable energy generation. It is designed in a small compact feature with a quiet mechanism and has no gas emission, enabling it to conserve energy and preserve the global environment. Iron disilicide ( β - F e S i 2 / S i ) composite materials prepared by eutectoid reaction is found promising for thermoelectric applications. The strategies to enhance the thermoelectric properties of these composites are mainly by conducting band structure engineering such as elemental doping and nanostructure engineering. This article reviews the effects of elemental doping and nanostructuring of β - F e S i 2 / S i composite materials. Mn and Co were found to be the most common dopants due to their contribution to carrier mobility and carrier concentration. Other dopant elements such as Al, introduced point defects on the composite structure that is effective in lowering thermal conductivity. P was also found to be effective on both electronic and lattice contribution of thermal conductivity. Furthermore, in thin films structure, flatter surface is highly recommended rather than the crystallinity of films to enhance carrier mobility and suppress thermal conductivity. Thus, the way to optimize β - F e S i 2 / S i composite materials were discovered by the significant number of studies on refinement of composite structure into nanoscale. From these studies, electrical conductivity value was significantly enhanced while reducing its thermal conductivity and Seebeck coefficient value. The deterioration of Seebeck coefficient is yet to be improved hence was estimated possible by introducing doping mechanisms. Therefore, this review concludes some potential strategies for improving Seebeck coefficient while simultaneously increasing electrical conductivity and decreasing thermal conductivity towards enhancing its thermoelectric performance.